2021
DOI: 10.3389/fonc.2020.606485
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs: Emerging Bladder Cancer Biomarkers and Targets

Abstract: Circular RNAs (circRNAs) are newly discovered intriguing RNAs due to the covalently closed loop structure, high stability, tissue specificity, and functional diversity. In recent years, a large number of circRNAs have been identified through high-throughput sequencing technology and bioinformatics methods, the abnormal expression of circRNAs are closely related to many diseases including bladder cancer (BC). CircRNAs have been proven to have several functions, such as acting as a regulator of parental gene tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…It is closely related to the occurrence and development of cancer. It can act as an mRNA 'sponge', regulate transcription and splicing, and interact with RNA-binding proteins (104). Most circRNA negatively regulates lymph node metastasis of bladder cancer, and some molecules positively regulate this process ( Figure 5).…”
Section: The Role Of Circrnas For Bca Lymph Node Metastasismentioning
confidence: 99%
“…It is closely related to the occurrence and development of cancer. It can act as an mRNA 'sponge', regulate transcription and splicing, and interact with RNA-binding proteins (104). Most circRNA negatively regulates lymph node metastasis of bladder cancer, and some molecules positively regulate this process ( Figure 5).…”
Section: The Role Of Circrnas For Bca Lymph Node Metastasismentioning
confidence: 99%
“…7,8 Several studies have shown that circRNAs are implicated not only in various physiological and autoimmune diseases, but also playing an important role in multiple malignant tumorigeneses, cell proliferation, cell cycle, apoptosis, and metastases (migration and invasion). [9][10][11] Dysregulated circRNAs have been linked to a number of pathological processes, including cancer development. 12 For example, hsa_circ_0007031 promotes tumor progression and fosters 5-fluorouracil resistance in colorectal cancer by regulating the miR-133b/ABCC5 axis.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs have a distinctive circular structure that enables them to act as miRNA sponges, control alternative splicing, bind to RNA‐binding proteins, and even encode proteins, thus regulating gene expression in a variety of ways 7,8 . Several studies have shown that circRNAs are implicated not only in various physiological and autoimmune diseases, but also playing an important role in multiple malignant tumorigeneses, cell proliferation, cell cycle, apoptosis, and metastases (migration and invasion) 9–11 . Dysregulated circRNAs have been linked to a number of pathological processes, including cancer development 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Poliseno et al first proposed the hypothesis of the interaction between protein-coding messenger RNAs (mRNAs) and ncRNAs [ 7 , 8 ] and circRNAs could act as ceRNAs [ 11 , 12 ]. Owing to the advantages of abundance, conservation, stability, and high specificity in serum, plasma, and other body fluids [ 13 , 14 ], circRNAs hold great potential as noninvasive blood-based biomarkers in cancer management [ 15 , 16 ]. A recent meta-analysis of the diagnostic efficacy of circRNAs in lung cancer tissues and blood suggested that circRNAs have diagnostic potential in the Chinese lung cancer population [ 17 ].…”
Section: Introductionmentioning
confidence: 99%